2014
DOI: 10.1071/fp13106
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of xerophyte Zygophyllum xanthoxylum ZxNHX and ZxVP1-1 enhances salt and drought tolerance in transgenic Lotus corniculatus by increasing cations accumulation

Abstract: Lotus corniculatus L. is an important legume for forage, but is sensitive to salinity and drought. To develop salt- and drought-resistant L. corniculatus, ZxNHX and ZxVP1-1 genes encoding tonoplast Na+/H+ antiporter and H+-pyrophosphatase (H+-PPase) from a succulent xerophyte Zygophyllum xanthoxylum L., which is well adapted to arid environments through accumulating Na+ in its leaves, were transferred into this forage. We obtained the transgenic lines co-expressing ZxNHX and ZxVP1-1 genes (VX) as well as expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 46 publications
8
60
0
Order By: Relevance
“…In recent years, the development of molecular biology and transgenic engineering provides tools for creation of new cultivars with enhanced stress tolerance (Hasegawa et al, 2000; Herrera-Estrella, 2000; Yang et al, 2010; Tang et al, 2015; Zhang et al, 2016). Numerous studies have demonstrated that (co-)overexpression tonoplast NHX or/and H + -PPase genes is one of the most effective strategies to create transgenic species with enhanced salt and drought tolerance through genetic engineering technology (e.g., Apse et al, 1999; Gaxiola et al, 2001, 2007; Zhao et al, 2006; Liu et al, 2010; Bhaskaran and Savithramma, 2011; Pasapula et al, 2011; Gouiaa et al, 2012; Bao et al, 2014; Bassil and Blumwald, 2014). To develop salt- and drought-resistant forage cultivar, we have co-transferred the tonoplast NHX and H + -PPase genes ( ZxNHX and ZxVP1-1 , respectively) from a xerophyte Z. xanthoxylum into the important legume forage alfalfa and successfully improved the salt and drought tolerance in T 0 generation transgenic plants (Bao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, the development of molecular biology and transgenic engineering provides tools for creation of new cultivars with enhanced stress tolerance (Hasegawa et al, 2000; Herrera-Estrella, 2000; Yang et al, 2010; Tang et al, 2015; Zhang et al, 2016). Numerous studies have demonstrated that (co-)overexpression tonoplast NHX or/and H + -PPase genes is one of the most effective strategies to create transgenic species with enhanced salt and drought tolerance through genetic engineering technology (e.g., Apse et al, 1999; Gaxiola et al, 2001, 2007; Zhao et al, 2006; Liu et al, 2010; Bhaskaran and Savithramma, 2011; Pasapula et al, 2011; Gouiaa et al, 2012; Bao et al, 2014; Bassil and Blumwald, 2014). To develop salt- and drought-resistant forage cultivar, we have co-transferred the tonoplast NHX and H + -PPase genes ( ZxNHX and ZxVP1-1 , respectively) from a xerophyte Z. xanthoxylum into the important legume forage alfalfa and successfully improved the salt and drought tolerance in T 0 generation transgenic plants (Bao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The better salt and drought tolerance of NHX and H + -PPase transgenic plants could be explained as a consequence of increased ion compartmentation into vacuole resulting from increased expression of NHX and H + -PPase (Gaxiola et al, 2001, 2007; Leidi et al, 2010; Bao et al, 2014; Yang et al, 2015). Because vacuolar compartmentation of cations (such as, Na + and K + ) is mediated by NHXs and H + -PPase provides the proton motive force for this process as a tonoplast H + pump (Apse et al, 1999; Zhang et al, 2001; Gaxiola et al, 2002; Kronzucker and Britto, 2011; Yamaguchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations